Genome-Wide Identification of Medicago Peptides Involved in Macronutrient Responses and Nodulation . Issue 4 (13th October 2017) - de Bang, Thomas C.; Lundquist, Peter K.; Dai, Xinbin; Boschiero, Clarissa; Zhuang, Zhaohong; Pant, Pooja; Torres-Jerez, Ivone; Roy, Sonali; Nogales, Joaquina; Veerappan, Vijaykumar; Dickstein, Rebecca; Udvardi, Michael K.; et al.
Abstract : Genome-wide annotation and RNA-seq analysis identify small secreted peptides responsive to nodulation and macronutrient limitations regulating root and nodule development in Medicago truncatula. Abstract: Growing evidence indicates that small, secreted peptides (SSPs) play critical roles in legume growth and development, yet the annotation of SSP-coding genes is far from complete. Systematic reannotation of the Medicago truncatula genome identified 1, 970 homologs of established SSP gene families and an additional 2, 455 genes that are potentially novel SSPs, previously unreported in the literature. The expression patterns of known and putative SSP genes based on 144 RNA sequencing data sets covering various stages of macronutrient deficiencies and symbiotic interactions with rhizobia and mycorrhiza were investigated. Focusing on those known or suspected to act via receptor-mediated signaling, 240 nutrient-responsive and 365 nodulation-responsive Signaling-SSPs were identified, greatly expanding the number of SSP gene families potentially involved in acclimation to nutrient deficiencies and nodulation. Synthetic peptide applications were shown to alter root growth and nodulation phenotypes, revealing additional regulators of legume nutrient acquisition. Our results constitute a powerful resource enabling further investigations of specific SSP functions via peptide treatment and reverse genetics.